2021
DOI: 10.21203/rs.3.rs-1034994/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Survey of Methylobacterium Species and Strains Reveals Widespread Production and Varying Profiles of Cytokinin Phytohormones

Abstract: BackgroundSymbiotic Methylobacterium strains comprise a significant part of plant microbiomes. Their presence enhances plant productivity and stress resistance, prompting classification of these strains as plant growth-promoting bacteria (PGPB). Methylobacteria can synthesize unusually high levels of plant hormones, called cytokinins (CKs), including the most active form, trans-Zeatin (tZ). ResultsThis study provides a comprehensive inventory of 46 representatives of Methylobacterium genus with respect to phyt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 77 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…Extraction, purification, and quantification of CKs were performed as previously described ( Kisiala et al, 2019) . Samples were extracted in 1 mL of Bieleski solution to which 29 stable isotope-labelled internal standards were added (20 ng of each of the deuterated internal standards, OlChemim Ltd. (Olomouc, Czech Republic)) corresponding to the different forms of CK that were scanned for as listed in previous studies (Supplementary Table 1) (Kisiala et al, 2019; Aoki et al, 2021; Bean et al,2021; Palberg et al, 2022) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction, purification, and quantification of CKs were performed as previously described ( Kisiala et al, 2019) . Samples were extracted in 1 mL of Bieleski solution to which 29 stable isotope-labelled internal standards were added (20 ng of each of the deuterated internal standards, OlChemim Ltd. (Olomouc, Czech Republic)) corresponding to the different forms of CK that were scanned for as listed in previous studies (Supplementary Table 1) (Kisiala et al, 2019; Aoki et al, 2021; Bean et al,2021; Palberg et al, 2022) .…”
Section: Methodsmentioning
confidence: 99%
“…For full scan analysis, each sample was run in negative ion mode over the mass range of m/z 80−600, at 35,000 resolutions, with automatic gain control (AGC) target of 3 × 10 6 , and maximum injection time (IT) of 128 ms. For metabolite selection, data files (as Thermo.RAW) were converted to mzXML file by ProteoWizard (Version 2.1) and uploaded to XCMS Online (https://xcmsonline.scripps.edu) to query significant differences among the metabolite profiles (Papaioannou et al, 2021; Rodríguez-Moro et al, 2022) . To ensure the sensitivity, reliability and validity of metabolite profiling analyses, specific internal standards were monitored in either negative (ABA) or positive modes (Benzylaminopurine), and samples were analyzed at three dilution levels (1x, 10x and 100x dilution factor) ( Aoki et al, 2019; Palberg et al, 2022) . The optimization tests showed that undiluted samples in negative mode were the most robust and so these parameters were selected for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%